Enhancing Nurse Performance by Improving Quality of Work Life, Knowledge and Attitude - Nur Hidayah; Alviane Tiara Putri (Universitas Muhammadiyah Yogyakarta, 2020)
Cases of medical errors in health care services are serious problems. In Indonesia, the incidence of work accidents still often afflicts nurses in hospitals. The prevalence of patient safety is still high. The research aimed to analyze the factors that affected nurse performance in the application of the patient safety system at the hospital. The sampling technique employed a total sampling of 40 people. Data analysis functioned the Partial Least Square. The results shew: a) The knowledge influenced on the nurse performance and the work-life quality, b) The attitude of nurses affected the quality of work-life, but did not affect performance. The knowledge was the most robust variable affected performance. Conclusion: to improve nurse performance, a hospital should enhance the knowledge, attitudes, and nurse quality work of life.